THU0361 Bone and Joint Disease in Mucopolysaccharidosis Involves Tlr4-Related Inflammation and Improves upon Treatment with Pentosan Polysulphate. (10th June 2014) - Simonaro, C.; Frohbergh, M.; Ge, Y.; Meng, F.; He, X.; DeAngelis, V.; Karabul, N.; Sόlyom, A.; Schuchman, E.
Abstract : Background: The mucopolysaccharidoses (MPS) comprise a group of lysosomal storage disorders (LSDs) resulting from inherited deficiencies of 11 specific glycosaminoglycan (GAG) degrading enzymes. In certain types of MPS (those without significant CNS involvement), bone and joint disease and progressively worsening contractures have the greatest negative influence on patients' quality of life, and lead to severe disability. We have previously shown that GAG storage leads directly to activation of the TLR4/TNF-alpha inflammatory pathway, and that inflammation is a major contributor to bone and connective tissue pathology in MPS[1]. This pattern of inflammation resembles that occurring in arthritis, and we feel that the naturally occurring MPS animal models provide excellent systems in which to study disease pathogenesis and treatment. By using TNF-alpha blocking agents, we were able to show a decrease in inflammatory cytokines and an associated improvement in bone and joint changes in MPS animals[2]. Currently, treatment approaches available for MPS patients do not prevent worsening of joint pathology. Objectives: We recently identified an FDA-approved drug, pentosan polysulphate (SP-54, PPS), which resulted in reduction in inflammatory cytokine levels and remarkable improvements in bone and joint disease, as well as overall physical functioning, in a rat model of MPS type VI. Our goal was to assess dose-related effects of the medication to further establish the basis for clinical trials. Methods: We previously reported the effects of daily oral PPS treatment in MPS VI rats. Here we compare results of using oral dosing vs. weekly subcutaneous (sc) injections. Four groups of MPS VI rats were treated with weekly sc PPS at human equivalent doses of 1, 2 and 4 mg/kg. Results: The most efficacious sc PPS dose was 2 mg/kg. Treatment of all MPS VI rats with weekly sc PPS for up to 6 months was safely tolerated. Conclusions: We propose that weekly subcutaneous injections of PPS will be efficacious and safe in MPS patients with joint disease, and a phase 1/2 clinical study is planned. Further assessment of the role of inflammation in joint pathology associated with MPS, along with exploration of MPS joint disease as a type of arthritis model are also topics of our group's continuing research. References: Simonaro C, et al., Mechanism of glycosamionglycan-mediated bone and joint disease. Am J Path. 2008;172 (1): 112-22. Eliyahu E, et al., Anti-TNF-alpha therapy enhances the effects of enzyme replacement therapy in rats with mucopolysaccharidosis type VI. PLoS One. 2011;6(8):e22447. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3340